Mental health in the UK during the COVID-19 pandemic: cross-sectional analyses from a community cohort study - Elizabeth Broadbent; Carol Coupland; Trudie Chalder; Kavita Vedhara; Ru Jia; Kieran Ayling; Adam Massey (BMJ Open)
Objectives Previous pandemics have resulted in significant consequences for mental health. Here, we report the mental health sequelae of the COVID-19 pandemic in a UK cohort and examine modifiable and non-modifiable explanatory factors associated with mental health outcomes. We focus on the first wave of data collection, which examined short-term consequences for mental health, as reported during the first 4–6 weeks of social distancing measures being introduced.Design Cross-sectional online survey.Setting Community cohort study.Participants N=3097 adults aged ≥18 years were recruited through a mainstream and social media campaign between 3 April 2020 and 30 April 2020. The cohort was predominantly female (n=2618); mean age 44 years; 10% (n=296) from minority ethnic groups; 50% (n=1559) described themselves as key workers and 20% (n=649) identified as having clinical risk factors putting them at increased risk of COVID-19.Main outcome measures Depression, anxiety and stress scores.Results Mean scores for depression (x- =7.69, SD=6.0), stress (x- =6.48, SD=3.3) and anxiety (x- = 6.48, SD=3.3) significantly exceeded population norms (all p<0.0001). Analysis of non-modifiable factors hypothesised to be associated with mental health outcomes indicated that being younger, female and in a recognised COVID-19 risk group were associated with increased stress, anxiety and depression, with the final multivariable models accounting for 7%–14% of variance. When adding modifiable factors, significant independent effects emerged for positive mood, perceived loneliness and worry about getting COVID-19 for all outcomes, with the final multivariable models accounting for 54%–57% of total variance.Conclusions Increased psychological morbidity was evident in this UK sample and found to be more common in younger people, women and in individuals who identified as being in recognised COVID-19 risk groups. Public health and mental health interventions able to ameliorate perceptions of risk of COVID-19, worry about COVID-19 loneliness and boost positive mood may be effective.